Integrons, a predictive biomarker for antibiotic resistance in acute sepsis: the IRIS study. (24th September 2021) - Barraud, Olivier; Guichard, Elie; Chainier, Delphine; Postil, Deborah; Chimot, Loïc; Mercier, Emmanuelle; Frat, Jean-Pierre; Desachy, Arnaud; Lacherade, Jean-Claude; Mathonnet, Armelle; Bellec, Frédéric; Giraudeau, Bruno; et al.
Abstract: Background: Considering the increase in MDR Gram-negative bacteria (GNB), the choice of empirical antibiotic therapy is challenging. In parallel, use of broad-spectrum antibiotics should be avoided to decrease antibiotic selection pressure. Accordingly, clinicians need rapid diagnostic tools to narrow antibiotic therapy. Class 1–3 integrons, identified by intI1–3 genes, are genetic elements that play a major role in antibiotic resistance in GNB. Objectives: The objective of the IRIS study was to evaluate the negative and positive predictive values (NPVs and PPVs, respectively) of intI1–3 as markers of antibiotic resistance. Methods: The IRIS study was an observational cross-sectional multicentre study that enrolled adult subjects with suspected urinary tract or intra-abdominal infections. intI1–3 were detected directly from routinely collected biological samples (blood, urine or intra-abdominal fluid) using real-time PCR. A patient was considered 'MDR positive' if at least one GNB, expressing acquired resistance to at least two antibiotic families among β-lactams, aminoglycosides, fluoroquinolones and/or co-trimoxazole, was isolated from at least one biological sample. Results: Over a 2 year period, 513 subjects were enrolled and 409 had GNB documentation, mostly Enterobacterales. intI1 and/or intI2 were detected in 31.8% of patients and 24.4% of patients were considered 'MDR positive'. The NPV of intI1 and/or intI2 as a marker of acquired antibiotic resistances was estimated at 92.8% (89.1%–95.5%). The NPVs for first-line antibiotics were all above 92%, notably >96% for resistance to third-generation cephalosporins. Conclusions: The IRIS study strongly suggests that the absence of intI1 and intI2 in biological samples from patients with GNB-related infections is predictive of the absence of acquired resistances.